Utilidad de la Citometría de Flujo par la detección de Pseudomonas aeruginosa productoras de metalo betalactamasas - Salinas Salcedo, Iván Alexander (2019)
ABSTRACT Considered one of the main opportunistic pathogens, Pseudomonas aeruginosa is the cause of a wide variety of nosocomial infections. Treatment is limited to certain classes of antibiotics, including carbapenems. Several phenotypic tests have been proposed for the screening of P. aeruginosa producing carbapenemases, which must be confirmed by molecular techniques and taking an average time of 55 hours between the collection for the culture and the delivery of the antibiogram report, being necessary to develop faster tests. In the present investigation, we seek to determine the usefulness of flow cytometry (CF) for the detection of P. aeruginosa producing metallo betalactamases (MBL) in two hours. We analyzed 35 isolates of P. aeruginosa characterized genotypically, with the Becton Dickinson Cell Viability Kit in the FACSCalibur instrument, using two treatments, one tube with Meropenem and the other Meropenem-EDTA, looking for an increase in fluorescence in the Meropenem-tube. EDTA We worked with 22 P. aeruginosa producers of MBL (18 with the blaIMP gene and 4 with the blaVIM gene) and 13 non-producers of MBL, genotypically confirmed. Using the ratio of fluorescence increase in non-living cells, T-student test showed significant difference between the producers of MBL and non-MBL (p: 0.002) and considering as a cut-off point a ratio greater than 1.6. Were detected 19/22 P. aeruginosa producers of MBL, giving 3 false negatives (2 blaIMP and 1 blaVIM) while 12/13 non-producers of MBL gave negative for CF, obtaining a false positive. Showing a sensitivity of 86.4%, a specificity of 92.3% and a positive predictive value (PPV) of 95%. Therefore, FC would constitute an alternative to phenotypically detect the production of metallo β lactamase in P. aeruginosa in 2 hours presumptively.